1978
DOI: 10.1007/bf01330902
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of inducible enzymes in irradiated yeast: UV effects on regulation and activity per cell

Abstract: The synthesis of two inducible enzymes in UV irradiated cells was determined during an 8 h postirradiation incubatin. In contrast to the reduction of synthesis shortly after irradiation the effect after a longer period of incubation depends on the radiation sensitivity of the strain. Since exposure inhibits division leading to different cell number in controls and irradiated samples the data are also analysed on a per cell basis. ta considerable increase of the activity per cell was observed. A maximum is reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The arginase assay has been described elsewhere (Gocke and Kiefer 1977) . The cells were always held under repressing conditions before and transferred to inducing medium immediately after exposure at a density of 3 x 10 7 cells/ml except when liquid holding recovery was to be investigated when induction was started after the holding period .…”
Section: 3 Enzyme Assay and Conduct Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The arginase assay has been described elsewhere (Gocke and Kiefer 1977) . The cells were always held under repressing conditions before and transferred to inducing medium immediately after exposure at a density of 3 x 10 7 cells/ml except when liquid holding recovery was to be investigated when induction was started after the holding period .…”
Section: 3 Enzyme Assay and Conduct Of Experimentsmentioning
confidence: 99%
“…to the structural gene (Gocke and Kiefer 1978) . It was suggested that radiationinduced division delay is an important parameter in this respect .…”
mentioning
confidence: 99%